PERANAN MODAL KULTURAL DAN STRUKTURAL DALAM MENCIPTAKAN KERUKUNAN ANTARUMAT BERAGAMA DI BALI: BELAJAR DARI BALI - Halimatusa’diah Halimatusa’diah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
Ahmadiyah events in Cikeusik, Shia in Sampang, until the case of Tanjung Balai, are various events of intolerance that often color the reality of our plural society. However, in some other areas with its diverse community, as in Bali, we can find a society that is able to maintain harmony among its diverse peoples and live side by side. This study aims to describe various factors that support inter-religious harmony in Bali. This review is important to overcome the various religious conflicts that occurred in Indonesia, as well as how to create harmony among religious followers. Using a qualitative approach, this study found that the creation of tolerance and harmony among religious believers in Bali, in addition influenced by historical model, also because Bali has a strong cultural capital and structural capital. Cultural capital in the form of local wisdom that is still maintained and also the harmony agents such as guardians of tradition and FKUB also play a major role in maintaining and creating harmony among religious followers in Bali G M T Detect language Afrikaans Albanian Arabic Armenian Azerbaijani Basque Belarusian Bengali Bosnian Bulgarian Catalan Cebuano Chichewa Chinese (Simplified) Chinese (Traditional) Croatian Czech Danish Dutch English Esperanto Estonian Filipino Finnish French Galician Georgian German Greek Gujarati Haitian Creole Hausa Hebrew Hindi Hmong Hungarian Icelandic Igbo Indonesian Irish Italian Japanese Javanese Kannada Kazakh Khmer Korean Lao Latin Latvian Lithuanian Macedonian Malagasy Malay Malayalam Maltese Maori Marathi Mongolian Myanmar (Burmese) Nepali Norwegian Persian Polish Portuguese Punjabi Romanian Russian Serbian Sesotho Sinhala Slovak Slovenian Somali Spanish Sundanese Swahili Swedish Tajik Tamil Telugu Thai Turkish Ukrainian Urdu Uzbek Vietnamese Welsh Yiddish Yoruba Zulu Afrikaans Albanian Arabic Armenian Azerbaijani Basque Belarusian Bengali Bosnian Bulgarian Catalan Cebuano Chichewa Chinese (Simplified) Chinese (Traditional) Croatian Czech Danish Dutch English Esperanto Estonian Filipino Finnish French Galician Georgian German Greek Gujarati Haitian Creole Hausa Hebrew Hindi Hmong Hungarian Icelandic Igbo Indonesian Irish Italian Japanese Javanese Kannada Kazakh Khmer Korean Lao Latin Latvian Lithuanian Macedonian Malagasy Malay Malayalam Maltese Maori Marathi Mongolian Myanmar (Burmese) Nepali Norwegian Persian Polish Portuguese Punjabi Romanian Russian Serbian Sesotho Sinhala Slovak Slovenian Somali Spanish Sundanese Swahili Swedish Tajik Tamil Telugu Thai Turkish Ukrainian Urdu Uzbek Vietnamese Welsh Yiddish Yoruba Zulu Text-to-speech function is limited to 200 characters Options : History : Feedback : Donate Close